INTEGRATING OF PYROCLASTIC FLOW HAZARD ASSESSMENT INTO ZONING SYSTEM OF GUNUNG MERAPI NATIONAL PARK - , ST. Agung Triono Hermawan, Dr. DJAROT SADARTHO WIDYATMOKO, M.Sc ([Yogyakarta] : Universitas Gadjah Mada, 2013)
As one of national parks in Indonesia, the GMNP (Gunung Merapi National park) has three functions mandated on the Law nu.5/1990 which are: (1) protection of supporting life system, (2) preserving of biodiversity and its ecosystem, and (3) sustainable utilization of natural resources and its ecosystem and should be managed through the zoning system. The GMNP has been greatly influenced by the Merapi volcano activity with the pyroclastic flow as the main hazard. Since, the scale of the existing hazard map issued by Kementerian ESDM is too small, this map is not appropriate to be used on the management of GMNP. Moreover, the existing zoning system of GMNP has not integrated with the pyroclastic flow assessment yet. Therefore this research was addressed to produce a more detail hazard (pyroclastic flow) map and a proposed zoning system integrated with this map along with the recommendations to improve the regulation. Through the morphology analysis method using DEM (2006 and 2010) with 15 m resolution, and historical events of Merapi eruption, the pyroclastic flow hazard map was produced. While the zoning system of GMNP was obtained through localizing, qualifying, and overlying of 6 factors: the pyroclastic flow assessment, biodiversity, plant succession, potential environmental services (ecotourism), important information extracted from the existing zoning system and regulation. The biodiversity and ecotourism data had already collected by the GMNPâs staff while the plant succession data was obtained from the interpretation of Aster VNIR imagery using NDVI. The pryoclastic flow map achieved on scale 1:30.000, has more detailed risk levels (high, medium, low, very low I and very low II) and can be properly used to construct the zoning system of GMNP. Based on the validation using the affected area obtained from SPOT 5 imagery, the pyroclastic flow assessment has two characteristics: suitable for the pyroclastic flow but not suitable for the pyroclastic surge and more sensitive on the high topography area such the landscape of GMNP. Hereinafter, the zoning system of GMNP integrated with the pyroclastic flow assessment could be obtained through the construction of the proposed zoning system in which the zoning system produces the additional zones which are the new sanctuary zone located on the southern part of GMNP area, the succession zone with the NDVI value from 0.5 to 1, and the volcanic activity zone located on the high risk area. Moreover, 4 point recommendations to improve the regulation (P.56/Menhut-II/2006) have been proposed related to the disposition of the specific zone.